You hold me and I$1 (Bll hold yous - Carson, Jo, 1946-; Cannon, Annie (New York : Orchard Books, 1992)
When a great-aunt dies, a young child finds comfort in being held and in holding, too.
"A Richard Jackson book."
Keywords: Death -- Fiction